Bibliometric analysis of articles published in journal of dental sciences from 2009 to 2020 - Fu-Hsuan Liu; Chuan-Hang Yu; Yu-Chao Chang (Elsevier, 2022)
The bibliometric analysis was conducted to evaluate the publication characteristics of Journal of Dental Sciences (JDS) from ScienceDirect Online between 2009 and 2020. The most common published article type in JDS was original articles. The top four highest number of published articles were related to oral and maxillofacial surgery, periodontology, endodontology, and oral pathology. The most productive geographic region for articles was Asia. Taiwan ranked in the highest country in terms of successful publication in JDS. The impact factor of JDS ranged from 0.107 in 2009 to 2.080 in 2020. As compared with years between 2009 and 2014, there was a significant increase in impact factor during 2015-2020 (P = 0.026). By this bibliometric analysis, JDS needs to attract more audience outside the Asia to gain the higher international influence.